Android-based Heart Rate and Blood Oxygen Level Monitoring System (Oximeter) - Saputra, Candra Deska; Yudhana, Anton (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
The development of increasingly modern technology makes it possible to create a more advanced tool. The health sector as one of the important components of life also does not escape the support of technology. One of its implementations is an android-based heart rate and oxygen level monitoring system (oximeter). Heart rate monitoring can be done by everyone by utilizing existing technological developments. Measurements are made using only the fingers of the hand as input. The purpose of this study was to determine the design of a research tool for a heart rate monitoring system and blood oxygen levels (oximeter) based on android. This measuring instrument uses a Max30100 sensor which is attached to one person's fingertip to detect a heart rate signal, then the data generated by the sensor is received by Arduino, after that it is forwarded to Bluetooth and displayed on the Android application, then it will be processed into beats per minute (BPM) and blood oxygen levels (SPO2) so that you can find out the results of heart rate and oxygen levels displayed on Android. Based on the results obtained in heart rate monitoring, it can work well so that it can be seen the results of measurements using a device made with a person in normal conditions the heart rate beats between 60 to 75 beats per minuteÂ (BPM) and oxygen levels (SpO2) which can beat between 95 to 100, while using pulse oximetryÂ results in normal body conditions the heart rate beats between 60 to 75 beats per minuteÂ (bpm) and oxygen levels (SpO2) which can be between 95 and 100 oxygen levels (SpO2).